Komunikasi Interpersonal Dengan Job Search Behavior - Ratna Novianti Solikhah; Wardatul Mufidah; Erma Nursanti (IDEA: Jurnal Psikologi, 2021)
This study was intended to prove the relationship between interpersonal communication and job-seeking behaviour for undergraduate students with fresh graduate status. The hypothesis proposed is that there is a positive relationship between interpersonal communication and job-seeking behavior for undergraduate students with new graduate status.The population of this research is job seekers who are fresh graduates from Bachelor of Strata 1 (S1) who are graduates from several universities in Jombang city region. The number of samples in this study consisted of 31 individuals. The sampling technique used is random sampling.The independent variable in this study is interpersonal communication which is expressed by a scale, while the dependent variable is job search behavior which is expressed by a scale, which is then analyzed using the SPSS (Statistical Package for Social Science) program. Data analysis utilized Pearson's product moment correlation analysis.The results of the analysis showed that the significance value of the correlation between interpersonal communication and job search behavior was rxy = 0.238 with a significance of 0.098 (one-tailed). The value is above 0.05, which means there is no relationship between interpersonal communication and job-seeking behaviour.This demonstrates that the hypothesis suggested in this study is rejected. Keywords: Interpersonal Communication; Job Seeking Behavior.